The Phenomenon of Refusing Covid-19 Booster Vaccination in Muara Sentosa Subdistrict, Sei Tualang Raso District Tanjungbalai City In 2022 - Nurul Lidya Ayu; Otniel Ketaren; Evawani Martalena Silitonga (Science Midwifery, 2022)
Coronavirus Disease 2019 (COVID-19) vaccination is a worldwide government policy program aimed at reducing its transmission, reducing the morbidity and death rate due to COVID-19, achieving herd immunity in the community (herd immunity) and protecting people from disease to remain socially and economically productive. The pros and cons color the ongoing COVID-19 vaccination program in various countries, including Indonesia. Vaccinations that are ongoing and are in the midst of the community are experiencing problems, there are still people who have not received the existence of the vaccine, including in Muara Sentosa Village, Sei Tualang Raso District, Tanjunbalai City, where the coverage of the COVID-19 booster vaccination is still very low. The purpose of the study is to find out the reasons for the refusal. This type of research is qualitative with in-depth interviews with informants consisting of the Lurah, Head of the Environment, Religious Leaders, Community Leaders, Vaccinator Officers, and residents. The results showed that the main cause of the phenomenon of rejection of COVID-19 booster vaccination in Muara Sentosa Village was the lack of public knowledge about the COVID-19 disease, COVID-19 vaccination and work constraints in terms of time and side effects of vaccines. For this reason, it is necessary to take action by the local government to advocate with relevant agencies to increase community knowledge and facilitate vaccine service time for the community according to their free time.